A humanização como estratégia de marketing no Instagram: estudo de caso da marca da boca rosa beauty - Monteiro, Dara Flávia Santos (Brasil, 2023)
The main objective of this study is to understand the humanization strategy of Boca Rosa Beauty on Instagram. The delimitation of the theme is centered on: identifying the brand’s marketing strategies during the reality show; analyzing the brand’s humanization strategies on Instagram three months after its elimination from the reality show; and comparing the humanization strategy with another beauty brand on the same platform. For this purpose, pieces from Boca Rosa Beauty published on Instagram were selected, from January 21, 2020 to February 25, 2020, and from February 26, 2020 to May 26 of the same year. With the intention of understanding the humanization strategy of Boca Rosa Beauty on Instagram during and after the elimination of the CEO and her great success that extends to current times. To support this research, a brief theoretical review is carried out involving emotional marketing, color psychology, media convergence, brand positioning, transmedia narrative, public recognition, consumer connectivity, product personification, content marketing, and posting frequency. In the analysis of Boca Rosa Beauty’s Instagram and its owner Bianca Andrade, actions were identified that generated value in the experiences that Bianca lived during the program, the influence of the public through colors, the recognition of the audience as a strategy to make the consumer feel part of the brand, like an ambassador, experiential connectivity which is the depth of the connection between customers and brands, the strategy of personifying products, authentic communication with consumers, and useful content. Making the necessary adjustments, this experience produces knowledge and especially confirmation regarding the use of digital media, which makes it possible to increase the brand’s reach, more easily reach market niches, and generate proximity to the public and value in the product.